The Feeding Ecology of the Blue Swimming Crab, Portunus pelagicus (Linnaeus, 1758), at Kung Krabaen Bay, Chanthaburi Province, Thailand - Chutapa Kunsook,; Nantana Gajaseni,; Nittharatana Paphavasit, (Tropical Life Sciences Research, 2014)
The natural diet of blue swimming crabs, Portunus pelagicus, was investigated from October 2008 to October 2009 using hand sampling and a crab gill net. The results showed that the major prey items in the stomach contents of P. pelagicus were teleost fish (29.61%), organic matter (20.69%), crustaceans (18.3%) and shelled molluscs (11.46%). Significant differences were found in diet composition between juvenile and mature crabs, between crabs inside and outside the bay and among seasons. In contrast, significant differences were not found between male and female crabs. Diet semula jadi ketam renjong, Portunus pelagicus, telah dikaji dari Oktober 2008 hingga Oktober 2009 menggunakan penyampelan tangan dan ‘crab gill net’. Keputusan telah menunjukkan bahawa pemangsa utama dalam kandungan perut P. pelagicus ialah ikan teleos (29.61%), bahan organik (20.69%), krustasia (18.3%) dan moluska bercangkerang (11.46%). Perbezaan ketara telah dijumpai dalam komposisi diet antara ketam juvenil dan matang, antara ketam di dalam dan di luar kawasan teluk dan antara musim. Secara kontranya, perbezaan ketara tidak dijumpai antara ketam jantan dan betina.